Tinjauan Yuridis Terhadap Pendaftaran dan Penerbitan Sertifikat Tanah Bengkok - Jannah, Lailatul; Tri Herawati, Mega; Rachmawati, Istiana (Jurnal Komunikasi Hukum, 2021)
Bengkok land is village property in the form of village land. This bent land is widely known as village treasury land or village property. The definition of bent land itself is not explicitly regulated in statutory regulations. The definition of crooked land is implicitly regulated by statutory regulations. Based on the explanation of Article 72 of Law Number 6 of 2014 concerning Villages (hereinafter referred to as the Village Law), it is stated that bent land is the result of business. The provisions in Law Number 6 of 2014 concerning Villages indicate that Village Treasury Land or village assets which include bent land are certified in the name of the Village Government. In addition, the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 1 of 2016 concerning Village Asset Management, regulates the same thing as Law Number 6 of 2014 concerning Villages. This research approach uses a statutory approach (statute approach) and a conceptual approach (conceptual approach). Based on the research results, which crooked land that is starting to lose its existence is certified in the name of the Village Government